Cross-talk entre las vías de Wnt5a y NF-kB en melanoma - Barbero, Gastón Alexis (2019)
Wnt5a is over-expressed in melanoma and contributes to the motility, invasion and metastasis of these cells. Our results indicate that Wnt5a activates the NF-kB pathway, promoting p65 phosphorylation and nuclear translocation, IKK complex phosphorylation and IkBa degradation. This process is dependent on ROR1 and Dvl2, members of the Wnt pathway, as well as on TRAF2 and NIK, members of the NF-kB pathway. This response requires Akt and its inhibition prevents the activation of p65. However, in the SK-Mel28 cell line Akt is dispensable and the response is mediated by PKCo and GSK3b. We also showed that through an autocrine loop Wnt5a regulates the expression and basal activity of NF-kB. Finally, Wnt5a increases NF-kB transcriptional activity and promotes the release of pro-inflammatory cytokines. In sum, we demonstrated a new role for Wnt5a in cancer that thanks to the activation of NF-kB, promotes the synthesis of inflammatory cytokines, contributing to create the inflammatory and immunosupressive conditions that would allow melanoma cells to evade the immune response in the tumor microenvironment. These findings strength the role of Wnt5a as a new and promissory therapeutic target in melanoma.